The Values of Moral Education in Serat Wulangreh Pupuh Gambuh - Suhail Ahmad Rasyid; Al-Faiz Muhammad Rabbany Tarman; Yusuf Rohmat Yanuri (Al-fiqh, 2026)
This study explores the values of akhlakul karimah contained in Serat Wulangreh Pupuh Gambuh, a classical Javanese literary work composed by Pakubuwana IV that aims to guide moral cultivation within society. The research is motivated by the need to strengthen moral education through local wisdom sources that integrate Islamic ethical principles with Javanese cultural heritage. Using a qualitative library research method, this study analyzes textual elements of Pupuh Gambuh supported by primary manuscripts and secondary scholarly literature. The findings reveal that Pupuh Gambuh contains essential moral values relevant to Islamic education, particularly those related to personal ethics such as honesty, humility, patience, prudence, and vigilance and social ethics, including kindness toward relatives, preserving others’ dignity, and maintaining trust. These values demonstrate the richness of Javanese literary tradition in providing ethical teachings that remain significant for contemporary character education.